Exploring the price of motor vehicle collisions – A compensation cost approach. (March 2020) - Shannon, Darren; Rizzi, Luis; Murphy, Finbarr; Mullins, Martin
Abstract: Motor Vehicle Collisions (MVCs) accounted for an economic cost of 242 billion in the United States in 2010. A significant portion (42%) was associated with factors considered for compensation estimates – medical costs, lost earnings and reduced household productivity. This study proposes a methodology that accounts for these costs by using expected compensation costs (ECCs). Our approach differs from prior studies as we consider all injuries suffered by an individual in the MVC, rather than only the 'most severe' injury. We estimate ECCs for each injured occupant by linking the injuries suffered with guidelines on injury compensations, allowing for ECCs to be linked directly with collision factors. To demonstrate the ECC system, we conduct a cross-sectional mediation analysis to study the relationships between collisions and compensation. delta-V (the change in a vehicle's speed pre- and post-crash) remains a primary factor in the severity of MVCs and so it serves as a focal point in our study. We find that some collision factors influence compensation estimates because of the effects of delta-V, while others influence ECCs regardless of delta-V. The ECC system we introduce can mitigate litigation risk and highlight future approaches to road safety, as it bridges the gap between crash characteristics, injuries suffered, and economic damage. Our results support policy recommendations that promote seatbelt use and warn against alcohol-impaired driving, and support the proliferation of safety-enabled vehicles whose technology can mitigate the economic damage associated with detrimental crash types. Highlights: Predicting Expected Compensation Cost (ECC) estimates using collision and occupant data ECC estimates consider all injuries suffered rather than solely considering 'most severe injury' Delta-V plays a primary role in increasing compensation, and influences other factors Certain crash factors influence ECCs regardless of influence of delta-V Mediation approach unveils influential links that would have otherwise gone unnoticed